2021
DOI: 10.1186/s13098-021-00722-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of continuous glucose monitoring system in patients with type 2 mellitus diabetic during hemodialysis treatment

Abstract: Background Studies highlight the inaccuracy of glycated hemoglobin (HbA1c) for the assessment of glycemic control in dialysis diabetics and suggest the use of continuous glucose monitoring (CGM) as an alternative. Of the CGMs, FreeStyle Libre® is the most used in worldwide, but there is still no consensus on its use in dialysis. Method A 3-week prospective study was performed with 12 patients comparing capillary and interstitial glucose during dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…[ 29 ] Other studies have also demonstrated a higher MARD in patients with type 2 diabetes on dialysis. [ 30 , 31 ] In addition, studies assessing CGM accuracy intentionally excluded patients with severely impaired renal function presumably due to lower accuracy. [ 32 ] The subjects with advanced CKD IV and V in our study were more prone to hypoglycemia (glucose < 70 mg/dl) and significant anemia (mean hemoglobin 8.2 g/dl) - two circumstances associated with a higher MARD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Other studies have also demonstrated a higher MARD in patients with type 2 diabetes on dialysis. [ 30 , 31 ] In addition, studies assessing CGM accuracy intentionally excluded patients with severely impaired renal function presumably due to lower accuracy. [ 32 ] The subjects with advanced CKD IV and V in our study were more prone to hypoglycemia (glucose < 70 mg/dl) and significant anemia (mean hemoglobin 8.2 g/dl) - two circumstances associated with a higher MARD.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy in patients on hemodialysis is not affected by hydration status measured via impedance spectroscopy ( 97 ). A small study in twelve patients ( 98 ) showed better MARD at the beginning of the dialysis treatment (r=0.731) compared to the end of the treatment session (r=0.513), and overall 90% of the paired measurments were in the zones A/B (clinically accurate or no risk from error) of the Clarke error grid. A recent study evaluating the Dexcom G6 CGM in patients with type 1 and type 2 diabetes during dialysis showed an overall MARD 13.8% (interquartile range 4.9-18.2%) when CGM was compared to matched SBGM measurements ( 99 ).…”
Section: Glucose Sensor Technologymentioning
confidence: 98%
“…Mean absolute relative difference (MARD) was 19.5% ± 13.2% for Freestyle Libre versus 8.1% ± 7.6% for Medtronic iPro2 (48). In a three-week study comparing the accuracy Freestyle Libre versus capillary blood glucose in 12 patients on haemodialysis, the MARD was found to be higher than people without ESKD (49). Only one study had evaluated the accuracy of Medtronic iPro2 ™ with Enlite ™ sensor in 40 patients on PD.…”
Section: Overview Of Cgmmentioning
confidence: 99%